Statistical scaling laws for chemical oscillators - Silva, Vinicius Barros da [UNESP] (Elsevier B.V., 2018)
Universality classes are defined for the nonlinear, oscillatory Belousov-Zhabotinsky (BZ) reaction. We examine the decay to asymptotic steady state for supercritical Hopf bifurcation by considering a phenomenological approach supported by numerical simulations and confirmed by a analytical description. The formalism is general and it is expected to be universal for systems exhibiting Hopf bifurcations. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Scaling properties; Critical exponents; Belousov-Zhabotinsky; Hopf bifurcation